Maternal and fetal metabolomic alterations in maternal lipopolysaccharide exposure‐induced male offspring glucose metabolism disorders. (27th September 2021) - Qing, Qiting; Huang, Lili; Sun, Wanxiao; Chen, Jing; Yu, Ningning; Chen, Yuanhua; Xu, Dexiang; Zhao, Mei
Abstract: Maternal lipopolysaccharide (LPS) exposure during pregnancy induces metabolic abnormalities in male offspring, but the underlying mechanisms remain unclear. The purpose of this study was to investigate the effects of maternal LPS exposure during pregnancy on metabolic profiling of maternal serum and male fetal liver using Liquid Chromatograph Mass Spectrometer techniques. From day 15 to day 17 of gestation, pregnant mice were administered intraperitoneal LPS (experimental group) (50 μg/kg/d) or saline (control group). On day 18 of gestation, maternal serum and male fetal liver were collected. After LPS exposure, levels of 38 and 75 metabolites, mainly glycerophospholipid and fatty acid metabolites, were altered in maternal serum and male fetal liver, respectively. It was found that in maternal serum and male fetal livers, the glycerophospholipids containing saturated fatty acids (SFAs) and the SFAs were upregulated, while the glycerophospholipids containing polyunsaturated fatty acids (PUFAs) and the PUFAs were downregulated. This concordance between maternal and fetal alterations in glycerophospholipid and fatty acid metabolites may be a metabolomic signature of the early intrauterine period and may provide insight into the mechanisms by which maternal LPS exposure induces disorders of glucose metabolism in male offspring.